Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Wang, Jun; Zhu, Xuexia; Sun, Yunfei; Gu, Lei; Wu, Yaping; Chen, Yafen; Yang, Zhou (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus (T. obscurus), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.